Концептуальне забезпечення реформування системи МВС України: мета, завдання та базові принципи в запропонованих проектах - Зозуля, І. В.; Zozulia, I. V.; Зозуля Ігор (Форум права. – 2009. – № 1. – С. 174–183, 2009)
Виконана оцінка мети, завдань і базових принципів постановочної частини запропонованих проектів Концепції реформування системи МВС України щодо їх спроможності, доказовості, спрямованості, слушності, обґрунтованості та реалізуємості.

The estimation of the purpose, tasks and main principles of originative part of the offered projects of the Concept of reforming of system of the Ministry of Internal Affairs of Ukraine concerning their consistency, obviousness, orientation, validity, circumstantiality and reliability is executed.

Выполнена оценка цели, заданий и базовых принципов постановочной части предложенных проектов Концепции реформирования системы МВД Украины относительно их состоятельности, доказательности, направленности, основательности, обоснованности и реализуемости.
Conceptual Maintenance of Reforming of System of the Ministry of Internal Affairs of Ukraine: the Purpose, Tasks and Main Principles in the Offered Projects
Концептуальное обеспечение реформирования системы МВД Украины: цель, задания и базовые принципы в предложенных проектах
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; Internal Affairs Agencies; органы внутренних дел; реформирование МВД; реформування МВС; reform of the Ministry of Internal Affairs